Adoção de práticas de Green Supply Chain Management: mecanismos de indução e a importância das empresas focais - Arantes, Ariana Fernandes [UNESP]; Jabbour, Ana Beatriz Lopes De Sousa [UNESP]; Jabbour, Charbel José Chiappetta [UNESP] (Associação Brasileira de Engenharia de Produção, 2014)
The goal of this study is to analyze how green supply chain management (GSCM) practices are induced, both internally and externally, by focal companies on their supply chains located in the Brazilian high-tech segment. Eight case studies are conducted through the triangulation of data sources: interviews, observations and secondary data collection. The findings reveal specific mechanisms for inducing GSCM practices internally and externally, the principal of which are environmental training, logistics activities, the selection and evaluation of suppliers and green marketing. The focal firm is also identified as the vector in this process, inducing the adoption of green supply chain practices in the chain as a whole.

Este artigo tem como objetivo analisar como práticas de Green Supply Chain Management (GSCM) estão sendo induzidas, tanto interna quanto externamente, por empresas consideradas focais em suas cadeias de suprimentos localizadas no Brasil e atuantes no segmento de alta tecnologia. Foram realizados oito estudos de casos por meio da triangulação de fontes de dados: entrevistas, observações diretas e obtenção de dados secundários. Há mecanismos específicos para induzir práticas de GSCM internamente e externamente e destacam-se os mecanismos: treinamento ambiental, atividades logísticas, seleção e avaliação de fornecedores e marketing verde. Constatou-se também que a empresa focal é o vetor nesse processo.
Adoption of Green Supply Chain Management practices: mechanisms of induction and the role of focal companies
Keywords: Green Supply Chain Management; Mecanismos de indução; Empresas de alta tecnologia; Brasil; Green Supply Chain Management; Induction mechanisms; High-tech companies; Brazil